Assessing the Resilience and Preparedness of Basic Education Teachers for Distance Learning During the Covid-19 Pandemic in Surigao del Sur, Philippines - Patan, Juvy P.; Patan, Romeo A.; Sangco, Resa Mae R. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study assesses the preparedness, challenges, and coping mechanisms of basic education teachers in Surigao del Sur, Philippines, for online learning during the Covid-19 pandemic. Methodology: A descriptive-evaluative quantitative design was employed, surveying 1,281 professional teachers from the divisions of Tandag City, Bislig City, and Surigao del Sur. Participants were selected through stratified and simple random sampling. Data were collected using a validated questionnaire and analyzed through correlation tests and one-way ANOVA in R and Jamovi software. Main Findings: Findings indicate that most teachers were moderately prepared for online learning but faced significant challenges, including limited access to technology, poor internet connectivity, and insufficient resources. Teacher readiness was strongly correlated with effective coping mechanisms, underscoring the importance of institutional support, collaboration, and adaptability. This study provides localized insights into the experiences of rural educators in the Philippines during a health crisis, emphasizing resilience and institutional backing in sustaining education. Novelty/Originality of this study: By highlighting the critical role of preparedness and adaptability, it offers practical recommendations for enhancing teacher support systems and mitigating future educational disruptions.